Influence of literature developed by Hafez Shirazi on poems of Mohammad Ali Shams-Al-Din - Mozafari, Soudabeh; Hosseini, Abdollah; Naemi, Zohreh; Mousa Nataj, Vahid (Revista Publicando, 2018)
Hafez Shirazi has influenced on most Arab-speaking scholars. Mohammad Ali Shamsaldin, Leonean poet had maximally influenced by Hafez. When we read book “Fi Shirazat” complied by Mohammad Ali Shams-Al-Din, we will found this important issue that he and Hafez smashed together. His odes in this book has indeed occurred by using his natural creative force. When reader looks at the volume of book “Fi Shirazat”, he can see the name of Hafez Shirazi in the right side of the book and name of Mohammad Ali Shas-Al-Din in the left side and expression “Shirazat” at the middle of both; consequently, he would find the clear technical and spiritual cooperation between both poems. This paper aims to prove the influence of Hafez on Mohammad Ali Shams-Al-Din according to French School; for this purpose, the author has sought for required references and books in national and international libraries; by analytical methodology, the poems of Mohamamd Ali Shams-Al-Din were analyzed and compared to Persian Poems of Hafez to prove that he has influenced by Hafez”™s Poets. Results of this study indicate that the influence of Hafez on Shams-Al-Din could be completely determined in his poems and only in his book called “Fi Shirazat”.